58.2k views
0 votes
If f(x)=x^2-1, and g(x)=x+2,then g(f(x))=

User Glenbot
by
5.1k points

1 Answer

3 votes

The function f (x) ;


\begin{gathered} x^2\text{ - 1 will be used to represent the value of x in the function g (x) } \\ \text{Hence, g(x) = x + 2 } \\ =g\mleft\lbrace f(x)\mright\rbrace =(x^2\text{ - 1 ) + 2} \\ =x^2\text{ -1+2 } \\ =x^2\text{ + 1} \end{gathered}
\begin{gathered} \text{The fuction represented in the given pattern now becomes : } \\ x^2\text{ + 0x + 1} \end{gathered}

User Taersious
by
4.7k points